PEMBELAJARAN DARING KITAB KUNING PADA MASA PANDEMI COVID-19 DI MADRASAH MASYARIQUL ANWAR CARINGIN - Siti Maryam; Aat Royhatudin; Desyi Rosita; Ahmad Hidayat (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2022)
Digital-based learning of the kitab kuning, in the midst of the Covid-19 Pandemic, is actually learning that integrates religious science and technology science, which involves direct interaction between teachers and students which is a factor and indicator of the success of the education being implemented. Because the teacher is actually able to make good and effective interactions by understanding the knowledge of religion and science, the student will find it easier to communicate and interact with the teacher. The purpose of the research is to explain that digital-based learning of the yellow book, part of the integration of science that is able to understand IT (Information Technology) and actualize religion as a scientific discipline in an integrative and comprehensive manner, so that students at Madrasah Tsanawiyah Masyariqul Anwar Caringin not only increase cognitive intelligence, psychomotor and affective but also spiritual intelligence which is actualized in life. Qualitative research methods by collecting data from interviews and documentation. The results of this study found that students with digital-based yellow book learning were able to understand religion comprehensively and effectively so that cognitive intelligence through digital book content assessment was able to be studied and understood, and with psychomotor intelligence students were able to read the contents of the book with elat (sharaf) skills. and e'rob (nahwu) as well as affective intelligence that students are able to contextualize the guidance of the contents of the book with the demands of the times, thus students not only increase individual piety but social piety in accessing information in accordance with the demands of the times and the needs of society